Finanztransaktionssteuer in kleiner Runde? Hat die Finanztransaktionssteuer in Europa eine Chance? - Alexander Burger (IUBH Internationale Hochschule, 2019)
– A financial transaction tax (FTT) compares to a value-added tax on financial transactions and financial services. This differs from the financial activity tax (FAT) that is raised on profits of financial companies or on profit-related remuneration of financial managers. An FTT is neither necessarily related to a certain kind of financial transaction or service, nor does it have a clear assessment base or a certain tax rate. These are decisions to be made during political discourse. Taxes, also an FTT, have the potential to reduce trading volumes. This can even lead to a closing down of markets that operated on small margins that can be devoured by an FTT. If such markets fulfill the economic assumptions of perfect competition, an FTT should be rejected by economic reasons. The fiscal aspect of an FTT depends on the participating countries, the assessment base and the tax rate. The European Union hasn't been able to design an EU-wide FTT; not even the complete Eurozone has agreed on an FTT so that ten countries are currently negotiating the project in an in-depth cooperation. The assessment base has already eroded, starting with shares, bonds and derivative products right after the world financial crisis, reaching a minimum compromise with only shares as an assessment base for the FTT. Negotiations are still ongoing so that even some exceptions from this assessment might be possible. Experience has shown that an FTT leads to evasive reactions. Sweden and France know very well about that, and that might be a reason why Sweden does not participate in the in-depth cooperation. The cooperation still lacks a decision about the tax rate, they still have to negotiate about the distribution of the tax revenues, as the smaller countries within the in-depth cooperation fear that the bureaucratic cost of an FTT might exceed their proceeds from this project. The successful implementation of an FTT - even only within the ten countries of the in-depth cooperation - seems doubtful.
Keywords: G18; G28; H27; 650; assessment base; Ausweichreaktionen; Banken; banks; Bemessungsgrundlage; Euro; FAT; Finanzaktivitätssteuer; financial activity tax; Finanztransaktionssteuer; financial transaction tax; financial transaction; Finanztransaktion; FTS; FTT; in-depth cooperation; Kapitalverkehrskontrollen; Spekulation; stamp tax; Stempelsteuer; Steuer; Steuerhinterziehung; Steuertarif; Steuerhöhe; tax; tax evasion; tax rate; Transaktionssteuer; transaction tax; vertiefte Zusammenarbeit